Nanofabrication: Programmable Bidirectional Folding of Metallic Thin Films for 3D Chiral Optical Antennas (Adv. Mater. 19/2017). Issue 19 (May 2017) - Mao, Yifei; Zheng, Yun; Li, Can; Guo, Lin; Pan, Yini; Zhu, Rui; Xu, Jun; Zhang, Weihua; Wu, Wengang
Abstract : In article number1606482, Wengang Wu, Weihua Zhang and co‐workers demonstrate the strong optical rotation effect of a single nanohelix, fabricated by a focused‐ion‐beam‐induced nano‐deformation technique. The fabrication method allows the nanometer‐thin metallic films to be folded in both directions at the nanoscale with minimum material damages. Using this technique, 3D nanohelixes with various parameters are designed and fabricated, and it is experimentally demonstrated that the polarization axis of light could be rotated by ±8 degrees by individual nanohelices with different curling directions.